Low Household Income Status and Death from Pneumonia in People with Type 2 Diabetes Mellitus: A Nationwide Study - You-Bin Lee; So Hee Park; Kyu-na Lee; Bongsung Kim; So Yoon Kwon; Jiyun Park; Gyuri Kim; Sang-Man Jin; Kyu Yeon Hur; Kyungdo Han; Jae Hyeon Kim (Diabetes & Metabolism Journal, 2023)
Background We explored the risk of death from pneumonia according to cumulative duration in low household income state (LHIS) among adults with type 2 diabetes mellitus (T2DM). Methods Using Korean National Health Insurance Service data (2002 to 2018), the hazards of mortality from pneumonia were analyzed according to duration in LHIS (being registered to Medical Aid) during the 5 years before baseline (0, 1–4, and 5 years) among adults with T2DM who underwent health examinations between 2009 and 2012 (n=2,503,581). Hazards of outcomes were also compared in six groups categorized by insulin use and duration in LHIS. Results During a median 7.18 years, 12,245 deaths from pneumonia occurred. Individuals who had been exposed to LHIS had higher hazards of death from pneumonia in a dose-response manner (hazard ratio [HR], 1.726; 95% confidence interval [CI], 1.568 to 1.899 and HR, 4.686; 95% CI, 3.948 to 5.562 in those exposed for 1–4 and 5 years, respectively) compared to the non-exposed reference. Insulin users exposed for 5 years to LHIS exhibited the highest outcome hazard among six groups categorized by insulin use and duration in LHIS. Conclusion Among adults with T2DM, cumulative duration in LHIS may predict increased risks of mortality from pneumonia in a graded dose-response manner. Insulin users with the longest duration in LHIS might be the group most vulnerable to death from pneumonia among adults with T2DM.